Some popular songs of the Spanish period and their possible use in the music program of our schools - Cauayani, Consejo V. 1914- (College of Education, University of the Philippines Diliman, 1954)
The melodies of songs which were popular during the Spanish period were presented in this study. Their possible application to the teaching of music in our public schools was suggested.